IDA’s Crisis Response Window : Lessons from Independent Evaluation Group Evaluations - Independent Evaluation Group (World Bank, Washington, DC, 2019)
From the 15th replenishment of the International Development Association (IDA15)through IDA18, the Crisis Response Window (CRW) evolved from a focus on economicshocks to include two other types of crises—natural disasters and public healthemergencies. The CRW was set up as a pilot under IDA15 to address repercussionsrelated to the global financial crisis on IDA countries. When established as a permanent part of IDA, it was amended to address the impact of natural disasters in addition to economic shocks. CRW coverage was expanded to include public health emergencies when the Ebola crisis erupted in 2014. This IEG synthesis paper takes stock of experience with IDA’s CRW, making use of IEG evaluative evidence. The paper synthesizes findings from existing evaluations and information on CRW performance during its pilot stage under IDA15 and subsequent IDA cycles, to inform stakeholders and promote learning. The audience for this paper is primarily internal, including management, Executive Directors (including the Committee on Development Effectiveness), and IDA deputies.